2002
DOI: 10.1890/0012-9615(2002)072[0365:pscads]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Predation Structures Communities at Deep-Sea Hydrothermal Vents

Abstract: The structure and dynamics of natural communities result from the interplay of abiotic and biotic factors. We used manipulative field experiments to determine the relative roles of abiotic conditions and biotic interactions in structuring deep‐sea (2500 m depth) communities along environmental gradients around hydrothermal vents of the eastern tropical Pacific Ocean (East Pacific Rise, at 9°50′ N). We tested (1) whether predation by crabs and fishes affects the recruitment of benthic species and subsequent com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(78 citation statements)
references
References 45 publications
3
75
0
Order By: Relevance
“…in the younger bush and a Nemertean and a polynoid worm in the older bush; Aharon & Fu 2003) clearly indicate the importance of local primary production to the nutrition of these species, although they are greatly 34 S-enriched relative to the tube worm tissues. These results are somewhat similar to those of Micheli et al (2002) who found that at hydrothermal vents on the East Pacific Rise, predators closely associated with the tube worms derive a majority of their nutrition from chemosynthetic material. However, unlike some of the invertebrate heterotrophs examined in Micheli et al (2002), which would consume tube worm tissue under their experimental conditions, the chemosynthetic production consumed by invertebrate heterotrophs at these cold seeps is unlikely to include tube worms.…”
Section: Heterotrophssupporting
confidence: 90%
“…in the younger bush and a Nemertean and a polynoid worm in the older bush; Aharon & Fu 2003) clearly indicate the importance of local primary production to the nutrition of these species, although they are greatly 34 S-enriched relative to the tube worm tissues. These results are somewhat similar to those of Micheli et al (2002) who found that at hydrothermal vents on the East Pacific Rise, predators closely associated with the tube worms derive a majority of their nutrition from chemosynthetic material. However, unlike some of the invertebrate heterotrophs examined in Micheli et al (2002), which would consume tube worm tissue under their experimental conditions, the chemosynthetic production consumed by invertebrate heterotrophs at these cold seeps is unlikely to include tube worms.…”
Section: Heterotrophssupporting
confidence: 90%
“…Even rare, these studies give nevertheless evidence of diVerences of diet within the genus (Van Dover and Lichtwardt 1986;Chevaldonné and Olu 1996;Janßen et al 2000;Escobar-Briones et al 2002;Micheli et al 2002;Phleger et al 2005;Kemp et al 2006;Macavoy et al 2008a, b). The diet of M. andamanica from deep-sea wood falls, shown here to ingest ligneous wood in large proportion, appears quite original or exceptional.…”
Section: Role Of the Resident Gut Microorganismsmentioning
confidence: 99%
“…(complete name is not mentioned) would be predators or scavengers (Chevaldonné and Olu 1996;Macavoy et al 2008a) while M. alvisca, M. subsquamosa, M. geyeri and another Munidopsis sp. appeared to have a mixed diet composed of organic debris of the sediment, polychaetes, limpets, crab larvae, and would also graze the bacteria of the bioWlms (Van Dover and Lichtwardt 1986;Escobar-Briones et al 2002;Micheli et al 2002;Phleger et al 2005). Nothing is reported about the diet of M. cascadia, M. yaquiensis, M. verrilli, and M. quadrata that are found associated to whale carcasses (Williams et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Egg capsules were collected from caged (6 mm mesh) and 20 uncaged basalt colonization blocks placed on the seafloor as part of a larger colonization 21 study (Micheli et al 2002;Mullineaux et al 2003). Nine blocks collected in beds of 22 vestimentiferan tubeworms or mussels, during the May 1998 cruise, contained egg 23 capsules with embryos and developing veligers.…”
Section: Identification Of a Defined Group Of Species -Rflp Design 22mentioning
confidence: 99%
“…Gastropod abundances 2 and ecological influence across the range of vent habitats make them key players in 3 structuring macrofaunal communities (e.g. Micheli et al 2002;Mullineaux et al 2003;4 Govenar et al 2004;Mills et al 2007). High abundances of gastropod larvae in the 5 plankton (Metaxas 2004;Mullineaux et al 2005), multiple modes of development (Lutz 6 et al 1984;Lutz et al 1986), and relative ease of larval identification (Mullineaux et al 7 1996) allow researchers to address questions such as: how do larval development and 8 behavior, and hydrodynamics combine to disperse and/or retain individuals (Lutz et al 9 1980;Marsh et al 2001;Adams and Mullineaux 2008); and what is the impact of 10 dispersal and recruitment on community structure and dynamics?…”
Section: Introduction 20mentioning
confidence: 99%